Increasing privacy and security by integrating a Blockchain Secure Interface into an IoT Device Security Gateway Architecture - Marko Šarac (Elsevier, 2021)
Internet of Things and Blockchain are considered two major technologies. Lower latency and a higher linked system number provide greater flexibility for remote execution of Internet of Things (IoT) applications. It is no secret that IoT devices often have insufficient computing capacity (both in terms of processing power and storage requirements) to support robust protection and encryption algorithms. The Internet of Things is facing many challenges such as poor interoperability, security vulnerabilities, privacy, and lack of industry standards. Cyber-attacks on IoT devices can have an impact on energy trading privacy and security. This paper suggests a method for introducing a basic interface to an IoT device’s security gateway architecture along with Blockchain to provide decentralization and authentication. It adds much-needed anonymity and versatility to IoT infrastructure, which is currently lacking. The solution enhances the reliability of data sent to remote services by applying compatible cryptographic algorithms to it before sending it. The solution’s benefits include compatibility with all IoT products and the ability to run any cryptographic algorithm on data that can be used for microgrid trading and can be initialized and securely transported over 5G or 6G network infrastructures. As a part of this work, a security procedure has been created that supports every cryptographic algorithm for all IoT devices in the network. In addition, the interface is guarded by the Blockchain technology which eliminates single control authority, records historical transactions performed by the IoT devices and provides a trust between devices.